The Pre-Kerma SeUlement: New Elements Throw Light on the Rise of the First Nubian Kingdom - Honegger, Matthieu (Boston, Massachusetts: TIMOTHY KENDALL, 2004)
The aim of this paper is to present the results of the excavations of the Pre-Kerma settlement, which is located a few IOlometres away from the site of the ancient city of Kerma. This senlement, which antedates the Kerma civilisation by sorne centuries, was already organised in a very coherent manner, implying the existence at that time of a well-organised society. It was probably part of the process of social evolution that led to the formation of the early Nubian kingdom. The settlement seems to have been abandoned following the progressive drying out of the branches of the Nile, flowing nearby. The population apparently then moved and relocated to the west, on the site of the ancient city of Kerma.